The comparative analysis of Java frameworks: Spring Boot, Micronaut and Quarkus - Maciej Jeleń; Mariusz Dzieńkowski (Journal of Computer Sciences Institute, 2021)
The aim of the work is a comparative analysis of three frameworks designed for building web applications for the Java programming language: Spring Boot 2.4.4, Micronaut 2.5.4 and Quarkus 1.13.4.Final. Test applications were prepared, equipped with the same functionality as used in the experiment consisting in measuring the server response times to a POST request – performing the data entry into the database. For each test application, the scenario aimed at measuring the time of handling requests under various load conditions was repeated five times. During each repetition of the scenario, the load which was the average number of requests sent per second by virtual users was increased. In parallel with performance tests, the reliability of the test applications was measured. Reliability was defined as the percentage of requests sent to the server that ended in a failure. The comparative analysis also took into consideration the volume of the code of the test applications based on the selected frameworks. The performed analyses showed that in terms of all the criteria considered in this work Micronaut proved to be the best framework.